SALES REPORT INFORMATION SYSTEM DESIGN WITH WATERFALL METHOD AT THE MOCIKEKE COMPUTER STORE - Rima Tamara Aldisa (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2024)
The Sales Report Information System is a system designed to collect, store, manage, analyze and present information related to the sale of a product or service. This system usually includes various types of sales data such as the number of items sold, sales price, customers who purchased, location of sales. This research aims to design and implement an effective information system for managing sales reports at the MociKeke Computer Store using the waterfall development method. The stages of the waterfall method, including requirements analysis, system design, implementation, testing, and maintenance, will be applied sequentially. This system will facilitate shop owners in managing and analyzing sales data efficiently with the aim of improving timely and accurate decision making. It is hoped that by implementing an appropriate information system there will be an increase in sales and operational efficiency and performance for the entire MociKeke Computer Store.